Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L) pada Berbagai Konsentrasi Pupuk NPK dan Jenis Media Tanam Secara Hidroponik NFT - Dinda M. Thessalonika Siregar; Fahri Ali; Desi Maulida; Erie Maulana; Nanang Wahyu Prajaka; Wika Anrya Darma (Politeknik Negeri Lampung, 2023)
NFT hydroponic is a plant cultivation technology that allows plant roots to grow on a shallow nutrient layer on the narrow field. The goal of this study was to evaluate the best NPK 16-16-16 fertilizer concentration and planting media, as well as the combination of the best NPK 16-16-16 fertilizer concentration and planting media, on the growth and yield of pakchoy (Brassica rapa L). This study used a split plot in factorial randomized block design. The first factor is the concentration of AB mix fertilizer as a control at 1400 ppm (N1) and the concentration of NPK fertilizer, namely: 758 ppm (N2), 1000 ppm (N3). The second factor element is the type of planting medium, which consists of 6 media: rockwool (M1), cotton (M2), sponge (M3), fern (M4), charcoal husk (M5), and cocopeat (M6), with 2 repetitions and 18 treatment combinations. Plant height (cm), number of leaves (pieces), leaf width (cm), leaf length (cm), wet weight of sample plants (grams), and dried weight of plants (grams) were the observation variables. In comparison to an NPK nutrient concentration of 1000 ppm, providing an NPK fertilizer concentration of 758 ppm resulted in better growth and yield in the parameters of number of leaves, wet weight, and dry weight of pak choy plants. Using husk charcoal as a planting medium resulted in superior growth and results in the plant height, number of leaves, leaf width, leaf length, and wet weight of pakchoy plants.